Integrated Torajan Indigenous Culture in English For Tourism Course - Nilma Taula’bi; Syarifuddin Dollah; Amirullah (Indonesian Journal Publisher, 2025)
This study explores the integration of Torajan indigenous culture into an English for Tourism (EFT) course to contextualize language learning while promoting cultural identity. Using a qualitative research and development (R&D) approach, cultural elements such as Rambu Solo’, Rambu Tuka’, Tongkonan houses, and Torajan proverbs were embedded into communicative English modules. Data were collected through needs analysis, interviews with lecturers and students, and pilot implementation. The findings indicate that integrating Torajan cultural content improves students’ tourism-related vocabulary, enhances motivation, and strengthens intercultural competence, while also reinforcing cultural pride. Challenges include limited availability of English-language materials on Toraja and the need for lecturer training in culturally responsive pedagogy. The study concludes that embedding indigenous culture in EFT fosters both global communication skills and sustainable cultural tourism